SAT0434 A TRANSIENT DECREASE IN SERUM URATE CHANGES THE CLINICAL TRAJECTORY OF SUBJECTS WITH ADVANCED GOUT. (June 2019) - Pillinger, Michael H.; Fields, Theodore; Yeo, Anthony; Lipsky, Peter
Abstract : Background: The standard approach to monitor subjects with gout is to measure serum urate. The assumption is that the signs and symptoms of disease will improve if serum urate is maintained below the target level of 6 mg/dL. However, there has been little emphasis on whether lowering urate transiently would have a prolonged impact on the clinical manifestations of advanced gout. Objectives: Assess the clinical benefit in patients with advanced gout who had transient lowering of serum urate resulting from treatment with pegloticase, a pegylated recombinant uricase. Methods: A post hoc analysis was carried out using the results from two randomized controlled trials (RCTs) of 6 months duration to assess the efficacy of treatment with 8 mg of pegloticase every 2 weeks (q2w) 1 . Serum urate was measured before each infusion and the serum urate area under the curve (AUC) was calculated as described 2 for the first and second three-month periods of time in the RCTs. The following clinical outcomes were assessed: gout flares, tophus reduction, patient global assessment (PtGA), tender and swollen joints (TJC and SJC), pain measured with a 100-mm visual analog scale (VAS) and a variety of patient reported outcomes (36-Item Short Form Health Survey [SF-36] Physical Component Score [PCS] and Arthritis-Specific Health Index Score [ASHIS]). Results: The analysis included 85 subjects treated with q2w pegloticase and 43 patients who received placebo. Of the 85 pegloticase-treated subjects, 49 had only a transient decrease in serum urate owing to the development of anti-pegloticase antibodies. The mean length of time these subjects experienced a serum urate <6 mg/dL was approximately 6 weeks 3 . Despite the transient reduction in serum urate, the serum urate AUC for the first and second 3 months of the RCTs was significantly (p=0.008) decreased compared to placebo-treated subjects. However, it was significantly (p<0.0001) less reduced compared with those with persistent urate lowering throughout the 6 month RCTs (Table 1 ). Results for both the subjects with persistent and transient lowering of serum urate to <6 mg/dL indicated significant reduction in tophi and improvements from baseline in PtGA, TJC, SJC, pain, and ASHIS after 6 months of the RCT. No significant improvements were observed in the patients who received placebo. Conclusion: A transient reduction in serum urate resulting from pegloticase therapy can result in significant clinical benefit lasting through the 6 months of the RCTs. These results suggest that transient lowering of urate can alter the trajectory of the clinical manifestations of advanced gout. Moreover, estimates of serum urate AUC may be more helpful in assessing the impact of urate lowering therapy than individual measurements of serum urate. References: [1] Sundy, JS, et al. JAMA. 2011; 306:711 [2] Mandell, BF, et al. Arthritis Research Ther. 2018; 20:286 [3] Lipsky, PE, et al. Arthritis Res Ther. 2014; 16:R60 Disclosure of Interests: Michael H. Pillinger Consultant for: Horizon Pharma, SOBI, Theodore Fields Consultant for: Horizon Pharma, Anthony Yeo Employee of: Horizon Pharma, Peter Lipsky Consultant for: Consulting fees from Horizon Pharma